Revisiting the Inverted Pyramid in Online News: kompas.com and theborneopost.com - Fikry Zahria Emeraldien; Alexander Choo; Cindy Melania Fitriani; El Haanim Nur Diny; Rada Putri Awaliyah (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The rapid growth of online media has significantly transformed news production and dissemination practices. In the digital era, news is no longer produced exclusively by professional journalists, resulting in increasing variation in newswriting styles and structures. Consequently, many online news articles no longer strictly adhere to the traditional inverted pyramid structure. This study examines the application of the inverted pyramid structure in online news articles published by Kompas.com (Indonesia) and The Borneo Post (Malaysia). Using a quantitative content analysis approach, this research analyzes the structural patterns of hard news and soft news across both media outlets. The findings reveal notable variations in the composition of news structures. While the inverted pyramid model remains generally observable, hard news articles in both media do not fully conform to its classical form. The lead section contains the most essential information in considerable detail, the middle section tends to be relatively brief, and the concluding section still presents substantively relevant content. Similarly, soft news articles demonstrate a more flexible structure, characterized by attention-grabbing leads, less elaborated middle sections, and broader conclusions intended to generate emotional resonance or deeper reflection. These results indicate a shift from a rigid inverted pyramid model toward a more adaptive and reader-oriented structure in contemporary digital journalism.